Immune status for monitoring and treatment of bladder cancer - Pan, Shen; Li, Shijie; Zhan, Yunhong; Chen, Xiaonan; Sun, Ming; Liu, Xuefeng; Wu, Bin; Li, Zhenhua; Liu, Bitian (Frontiers in Immunology, 2022)
The high recurrence rate of non-muscle invasive bladder cancer (BC) and poor prognosis of advanced BC are therapeutic challenges that need to be solved. Bacillus Calmette-Guerin (BCG) perfusion was the pioneer immunotherapy for early BC and the discovery of immune checkpoint inhibitors has created a new chapter in the treatment of advanced BC. The benefit of immunotherapy is highly anticipated, but its effectiveness still needs to be improved. In this review, we collated and analysed the currently available information and explored the mechanisms by which the internal immune imbalance of BC leads to tumour progression. The relationship between immunity and progression and the prognosis of BC has been explored through tests using body fluids such as blood and urine. These analytical tests have attempted to identify specific immune cells and cytokines to predict treatment outcomes and recurrence. The diversity and proportion of immune and matrix cells in BC determine the heterogeneity and immune status of tumours. The role and classification of immune cells have also been redefined, e.g., CD4 cells having recognised cytotoxicity in BC. Type 2 immunity, including that mediated by M2 macrophages, Th2 cells, and interleukin (IL)-13, plays an important role in the recurrence and progression of BC. Pathological fibrosis, activated by type 2 immunity and cancer cells, enhances the rate of cancer progression and irreversibility. Elucidating the immune status of BC and clarifying the mechanisms of action of different cells in the tumour microenvironment is the research direction to be explored in the future.